Fontes potássicas na produção do pimenteiro em substrato fertirrigado - Abrahão, Camila [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Excess fertilizer can cause damage in sweet pepper cultivation and to the environment. Therefore, the choice of fertilizer and the application of a balanced nutrient solution are essential for the production and quality of the final product. Thus, the aim of the present study was to evaluate the effects of increasing potassium fertilizer, using different potassium sources and doses in the production of fertirrigated sweet pepper grown in substrate under greenhouse conditions as well as monitor the nutritional status of pepper through methods alternative. The characteristics evaluated were: EC and pH of the substrate solution, nitrate and potassium levels in the solution of the substrate and the sap of plants, macro and micronutrients in the leaf dry mass, SPAD index, number of total and marketable fruit, total production and commercial fresh mass, length and diameter of the fruits and the correlations between these variables. The experiment was conducted under 4 experimental design of randomized blocks in a factorial 4 x 2 + 1, constituting 9 treatments, with four repetitions. The treatments consisted of two sources potassic (KCl and K2SO4), four potassium doses (125, 250, 375 and 500 mg L-1) and more control (0 mg L-1). It was observed that the dose of 300 mg L-1 K, regardless of the source used, higher total production and commercial hybrid sweet pepper Platero. The EC of treatment with KCI has reached value of 5.0 dS m-1, while with K2SO4 the maximum value was 3.5 dS m-1, both the higher dose. The application of KCl increased number of fruits compared to K2SO4. Treatment with K2SO4 presented to both the 75 and 165 DAT, higher concentration of poatassium on the dry weight of leaves and of sulfur to DAT 165. A higher concentration of NO3- in the substrate solution occur with K2SO4 relative to KCl to 75 DAT, and to 165 DAT higher concentration of potassium in the substrate solution in the same ...

O excesso da adubação pode causar prejuízos na cultura do pimenteiro e danos ao meio ambiente. Por isso, a escolha do fertilizante e a aplicação de uma solução nutritiva equilibrada são fundamentais para a produção e qualidade do produto final. Assim, objetivou-se com o presente trabalho avaliar os efeitos do incremento da adubação potássica, utilizando diferentes fontes e doses potássicas na produção dos frutos de pimenteiro fertirrigado cultivado em substrato sob ambiente protegido, bem como monitorar o estado nutricional do pimenteiro por meio de métodos alternativos. As características avaliadas foram: CE e pH da solução do substrato, teores de nitrato e potássio na solução do substrato e na seiva das plantas, teores de macro e micronutrientes na massa seca foliar, índice SPAD, número de frutos total e comercial, produção total e comercial, massa fresca, comprimento e diâmetro dos frutos e as correlações entre essas variáveis. O experimento foi conduzido sob delineamento experimental de blocos ao acaso, em esquema fatorial 4 x 2 + 1, constituindo 9 tratamentos, com 4 repetições. Os tratamentos foram constituídos por duas fontes potássicas (KCl e K2SO4), 4 doses de potássio (125, 250, 375 e 500 mg L-1) e mais o controle (0 mg L-1). Observou-se que a dose de 300 mg L-1 de K, independente da fonte utilizada, proporcionou maior produção total e comercial do pimenteiro híbrido Platero. A CE no tratamento com KCl atingiu valor de 5,0 dS m-1, enquanto que com o K2SO4 o valor máximo foi de 3,5 dS m-1, ambos com ...
Sources of potassium in the production of fertigated sweet pepper in substrate
Keywords: Pimentão - Cultivo; Fertirrigação; Potassio na agricultura; Potassium in agriculture